SANCTIONS FOR VETERINARY MALPRACTICES - Asmie Dianawati (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
Professional crime can occur in the health sector, including among veterinarians. This professional crime is in the form of malpractice. Malpractice is the failure to use skills and knowledge that are common or fulfill the rules in their actions as a medical profession according to standards in the same environment. If it's true that a veterinarian has committed malpractice, can he be penalized? With the normative juridical method, it is answered that veterinarians who commit malpractice can be subject to legal sanctions in accordance with the Civil Code. There are elements that must be met to determine that an event is malpractice.